Simultaneous low- and high-mass star formation in a massive protocluster: ALMA observations of G11.92-0.61 - Cyganowski, Claudia J.; Kruijssen, Diederik (Arxiv, 2017)
We present 1.05 mm ALMA observations of the deeply embedded high-mass protocluster G11.92-0.61, designed to search for low-mass cores within the accretion reservoir of the massive protostars. Our ALMA mosaic, which covers an extent of ~0.7 pc at sub-arcsecond (~1400 au) resolution, reveals a rich population of 16 new millimetre continuum sources surrounding the three previously-known millimetre cores. Most of the new sources are located in the outer reaches of the accretion reservoir: the median projected separation from the central, massive (proto)star MM1 is ~0.17 pc. The derived physical properties of the new millimetre continuum sources are consistent with those of low-mass prestellar and protostellar cores in nearby star-forming regions: the median mass, radius, and density of the new sources are 1.3 Msun, 1600 au, and n(H2)~10^7 cm^-3. At least three of the low-mass cores in G11.92-0.61 drive molecular outflows, traced by high-velocity 12CO(3-2) (observed with the SMA) and/or by H2CO and CH3OH emission (observed with ALMA). This finding, combined with the known outflow/accretion activity of MM1, indicates that high- and low-mass stars are forming (accreting) simultaneously within this protocluster. Our ALMA results are consistent with the predictions of competitive-accretion-type models in which high-mass stars form along with their surrounding clusters.
Gesehen am 19.10.2017